PROMOTING INCIDENTAL VOCABULARY LEARNING THROUGH VERBAL DRAMATIZATION OF WORDS - Looi-Chin Ch’ng (University of Kuningan, 2014)
Abstract: Despite the fact that explicit teaching of vocabulary is often practised in English as a Second Language (ESL) classrooms, it has been proven to be rather ineffective, largely because words are not taught in context. This has prompted the increasing use of incidental vocabulary learning approach, which emphasises on repeated readings as a source for vocabulary learning. By adopting this approach, this study aims to investigate students’ ability in learning vocabulary incidentally via verbal dramatization of written texts. In this case, readers’ theatre (RT) is used as a way to allow learners to engage in active reading so as to promote vocabulary learning. A total of 160 diploma students participated in this case study and they were divided equally into two groups, namely classroom reading (CR) and RT groups. A proficiency test was first conducted to determine their vocabulary levels. Based on the test results, a story was selected as the reading material in the two groups. The CR group read the story through a normal reading lesson in class while the RT group was required to verbally dramatize the text through readers’ theatre activity. Then, a post-test based on vocabulary levels was carried out and the results were compared. The findings revealed that incidental learning was more apparent in the RT group and their ability to learn words from the higher levels was noticeable through higher accuracy scores. Although not conclusive, this study has demonstrated the potential of using readers’ theatre as a form of incidental vocabulary learning activity in ESL settings.Keywords: incidental vocabulary learning, readers’ theatre, language learning